2011
DOI: 10.1364/ome.1.001409
|View full text |Cite
|
Sign up to set email alerts
|

Influence of symmetry breaking in pentamers on Fano resonance and near-field energy localization

Abstract: Arrays of asymmetric pentamers are designed and fabricated with an offset of the central nano-disk position to study the effect of symmetry breaking in pentamers. It is found that while planar symmetric oligomers can exhibit a single Fano Resonance (FR), an offset of the central nano-disk at a controlled gap of 3 nm from the nearest neighbor nano-disk, gives rise to the appearance of an additional dark mode that can potentially be used in localized surface plasmon resonance sensing. It is shown that this mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 22 publications
1
37
1
Order By: Relevance
“…43,44 It is shown that Fano-like resonances can be generated by deconstructing plasmonic nanoclusters, 45,46 and multiple Fano resonances can be obtained via this approach. 47 It also demonstrates that because of the excitation of higher order dark modes, multiple Fano resonances are generated in enlarged oligomer clusters. 20 However, there is a large energy gap between the multiple Fano resonances, which is unfavorable for SERS application.…”
Section: Introductionmentioning
confidence: 93%
“…43,44 It is shown that Fano-like resonances can be generated by deconstructing plasmonic nanoclusters, 45,46 and multiple Fano resonances can be obtained via this approach. 47 It also demonstrates that because of the excitation of higher order dark modes, multiple Fano resonances are generated in enlarged oligomer clusters. 20 However, there is a large energy gap between the multiple Fano resonances, which is unfavorable for SERS application.…”
Section: Introductionmentioning
confidence: 93%
“…In this work, the RLC circuit shown in Fig. 7(a) is used for this purpose; the mathematical model of this RLC circuit is similar to that of the mass-spring oscillator developed in [53] to model two distinct Fano resonances. The spectrum of the power drawn by the RLC circuit can be used to mathematically imitate the extinction CS spectrum of the designs with two plasmon modes D 2 and Q 1 (Section 2.2) and three plasmon modes D 3 , D 4 , and Q 2 (Section 2.3).…”
Section: Rlc Circuit Modelmentioning
confidence: 99%
“…It is well known that any physical Fano resonance can be mathematically modeled using a multi-resonance coupled system of oscillator equations [35]. To this end, the mass spring model has been accurately applied in explanation of one or two Fano resonances observed in the extinction cross-section (CS) spectrum of various nano-scale devices [35,[42][43][44]53].…”
Section: Introductionmentioning
confidence: 99%
“…The plasmonic Fano-like resonances exhibit sharp resonance and strong light confinement and are analogues of electromagnetically induced transparency (EIT) [1]. They have been observed in various symmetric and asymmetric metallic nanostructures that include nanoshells [2][3][4][5][6], multilayered nanocones [7], rings [8][9][10][11][12], dimers [13][14][15][16][17][18][19][20], trimers [21,22], quadrumer [23,24], pentamers [25,26], hexamer [27], and nanoparticle chains [28,29]. Among all the nanostructures, the plasmonic layered nanostructures have attracted many researchers attention because these structures exhibiting multiple Fano resonances over the entire visible spectrum as well as near to mid infrared region.…”
Section: Introductionmentioning
confidence: 99%